Mapping Global Trends and Research Frontiers in Developmental Assets: A Bibliometric Study - Syauqila, Ghina (Proceeding International Conference on Religion, Science and Education, 2026)
Youth are often regarded as period of heightened vulnerability, during which challenges arise from various domains. These conditions increase youth’s susceptibility to multiple risks, particularly the deterioration of mental health. Therefore, youth require a set of protective factors known as developmental assets, which consist of internal assets (positive identity, positive values, commitment to learning, and social competencies) and external assets (support, empowerment, boundaries and expectations, and constructive use of time). However, the study using the developmental assets framework, as a conceptual model within positive psychology that has emerged over the past two decades, remains relatively limited. Through bibliometric analysis, this study aims to map and reveal global research trends on developmental assets to identify research gaps and recommend directions for future scientific advancement. The analysis included 994 articles retrieved from Scopus and ScienceDirect databases. Article identities, such as publication year, country, and journal outlet were extracted. Research foci and trends were mapped using VOSviewer and further interpreted through a thematic approach. The findings revealed a steady growth of developmental assets researh, accompanied by eleven thematic clusters spanning identity development, mental health, risk and resilience, ecological systems, and youth-specific vulnerabilities. Geographically, the field remains dominated by Western countries, with limited contributions from non-Western contexts. Overall, the study underscores the expansion of this research area while highlighting the need for more culturally diverse and context-sensitive investigations.